TINJAUAN HUKUM PERDATA TERHADAP KEBIJAKAN KONSINYASI BERDASARKAN UNDANG-UNDANG RI NOMOR 2 TAHUN 2012 TENTANG KEWENANGAN NEGARA TERHADAP PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Maslon Hutabalian (Jurnal Komunikasi Hukum, 2022)
Land procurement for public interest based on Law No. 2 Year 2012 Activities held land by giving compensation decent and fair for those who are eligible, the land acquisition is an activity undertaken by the private sector and the government in order to get a piece land allocated for the implementation of a specific development. This research is descriptive analysis with normative juridical approach, ie an approach to legislation related to land acquisition, so as that at issue in this study is how the rule of law to the public shareholders Certificate of Ownership (SHM) is a land in the consignment policy associated with state authority in the procurement of land for public purposes under Law No. 2 In 2012, What are the factors inhibiting the provision of land and how to overcome obstacles facing the government in the procurement of land for public purposes and how the legal protection of individuals (people) who have policies consignment on a piece of land without their prior agreement. Based on research that land procurement for public interest implemented by the government must have legal certainty for holders of land rights, the rule of law in this case means that the government can not impose its authority to waive or revoke ownership rights of a holder of rights on land allocated for public use without first taking care of right holders in terms of social aspects and of the economic aspect, so that the individual holders of land rights can extend their life better than before its release or revoked, then the government must be able to guarantee legal protection for individuals/ communities experiencing problems law, particularly in the context of land acquisition for public purposes, which individuals/ communities of the poor do not have the power to block any government action that seemed to rape their human rights.